Drug discovery research (Wiley-Interscience, 2007)
Post Genomics Drug Discovery and Research explores and discusses some of the most important topics in post-genomics life and biopharmaceutical sciences. It provides an introduction to the field, outlining examples of many techniques currently used, as well as those still under development, which are important for the research of biopharmaceutical discovery in the post-genomics era.